Pengungkapan Diri dan Manajemen Privasi Komunikasi Pasien Covid-19 - Andi Pajolloi Bate; Haekal Fajri Amrullah (FISIP Universitas Atma Jaya Yogyakarta, 2022)
This study elaborates communication privacy management (CPM) theory in describing the privacy management of Covid-19 patients. This research uses case study method. The results show that informants who are worried about isolation and social stigma consider their status as a Covid-19 patient as personal information. Meanwhile, those who has the intention to participate in stopping the spread of Covid-19 consider their status as public information, so disclosure is necessary. Social media is considered as an appropriate means of disclosure because the patients get virtual support, minimal boundary turbulence, and the presence of healthy discussions about Covid-19 within it.